Tracing pottery-making recipes in the prehistoric Balkans 6th-4th millennia BC - Amicone, Silvia; Quinn, Patrick S. (Patrick Sean); Maric, Miroslav; Mirkovic-Maric, Neda; Radivojevic, Miljana (Archaeopress archaeology., 2019)
Balkan ceramic studies is an emerging field within archaeology. This book brings together diverse studies by leading researchers and upcoming scholars, capturing the variety of current archaeological, ethnographic, experimental and scientific studies on Balkan ceramic production, distribution and use.